Fiddling with the blue carbon: Fiddler crab burrows enhance CO2 and CH4 efflux in saltmarsh. (November 2022) - Agusto, Laura E.; Qin, Guoming; Thibodeau, Benoit; Tang, Jianwu; Zhang, Jingfan; Zhou, Jinge; Wu, Jingtao; Zhang, Lulu; Thapa, Poonam; Wang, Faming; Cannicci, Stefano
Graphical abstract: Highlights: How fiddle crab burrows affected the soil GHGs effluxes was assessed. Crab burrow volume in the vegetated salt marsh was smaller than in the mudflat. Crab activities could enhance coastal wetland CO2 efflux. With crab disturbances, soil CH4 efflux increased significantly. Fiddler crabs play an important role in coastal blue carbon sequestration. Abstract: Saltmarshes are important global carbon (C) sinks, but the considerable uncertainty in the C budget and the underlying mechanisms limit the estimation of greenhouse gas emissions (GHG, e.g., CO2 and CH4 ) in the context of global climate change. To ascertain the mechanistic understanding, we assessed how crab burrows morphology and greenhouse gas effluxes changed in response to interactions of fiddler crab burrow density, soil organic matter content (high vs low), and presence/absence of Spartina alterniflora (vegetated saltmarsh vs nearby unvegetated mudflat) on the coast of New England (USA). The crab burrow volume in the vegetated saltmarsh was smaller than that in the mudflat, and crab burrow volume greatly correlated with soil CO2 efflux, indicating that crab activities could enhance coastal wetland CO2 efflux. Soil CO2 and CH4 effluxes rates were significantly positively correlated with crab burrow density, organic matter content, and vegetation types. Specifically, the higher soil organic matter content and crab burrow density greatly increased soil heterotrophic respiration in the saltmarsh. Overall, with crab disturbances, soil CO2 and CH4 efflux increased by 32.1% and 47.9%, respectively. This study highlights that fiddler crab burrowing activity plays an important role in the C sequestration of coastal blue C ecosystems (BCEs).